Studies on Lactic Acid Bacteria Isolate Sr 13 From Bali Cattle Gastric - Siddhi, Bagus Nanda Govinda Muria; Suardana, I Wayan; Antara, Nyoman Semadi (Journal of Veterinary and Animal Sciences; Vol 2 No 1 (2019), 2019)
Lactic acid bacteria (LAB) is a generic term for bacteria that ferment lactose and produce lactic acid as its main product. In general, lactic acid bacteria belonging to Gram positive bacteria, negative catalase, does not form spores, have no cytochrome, aerotolerant, anaerobic to microaerophilic, require complex nutrients such as amino acids, vitamins (B1, B6, B12 and biotin), purine, pyrimidine. This study aims to determine the species of lactic acid bacteria (LAB) from isolate SR13 isolated from rumen liquid of bali cattle. The identification was started by cultivation of isolate on de Man, Rogosa, Sharpe (MRS) medium with anaerobic condition, confirmation of isolates by Gram staining and catalase test, and  finally identificion of species  by using conventional test and 50CH API test kit.  The results of study showed, the isolate of LAB SR 13 was detected as Pediococcus/Enterococcus , moreover, identification by using  50CH Api test kit  showed as Pediococcus pentosaceus 2